ACCELERATING POST-PANDEMIC RECOVERY: THE STRATEGIC ROLE OF CIVIL SOCIETY IN BALI - Gede Indra Pramana (Jurnal Penelitian Politik, 2025)
Since 2019, the COVID-19 pandemic has significantly impacted people’s lives; whether in terms of economy, socio-political life, or culture. Impact of the economic downturn was especially felt by inhabitants of Bali Island, who relied on tourism as their primary source of livelihood. After nearly two years of dealing with the pandemic, however, it seemed that The state’s strengthened role was not enough to completely mitigate this situation. This paper argues that civil society possesses a strategic position that allows them to play an essential role in helping the process of socio-economic recovery. Drawing from case studies, this study also suggested that the position of adat (traditional customs and institutions), as an element of Balinese civil society, was vital given their unique position. The strategic position of adat was demonstrated by the fact that the government enlisted the help of adat institutions to mitigate the impact of the pandemic, as shown by the mobilization of Pecalang (Balinese traditional security units) to enforce restrictions on population mobility. Moreover, the traditional village provided the basis for recovery through the formation of the Gotong Royong Task Force for Traditional Villages, as well as the recruitment of village volunteers. Learning from the Bali case, this research shows that civil society has great potential to overcome the COVID-19 pandemic.